Phenotypic variation and simultaneous selection of leaves/plant and seed mass in Jute mallow (Corchorus olitorius): Phenotypic variation and simultaneous selection of leaves/plant and seed mass in Jute mallow (Corchorus olitorius) - Adekoya, Modinat Adejoke; Adeniji, Olawale Taiwo; Ekanem, Ukoabasi Okon; Badmus, Abimbola Adeshile; Olosunde, Opeyemi Busayo; Peter, Jonah Melangu (Journal of Agricultural Sciences (Belgrade), 2024)
Corchorus olitorius is a leaf vegetable cultivated for the mucilage in the leaves. Leaf number, leaf length, and leaf width are popular market traits for this vegetable. Knowledge of the direct and indirect contribution of traits to leaf number and seed yield is least understood. Forty-two accessions of jute mallow were evaluated in a randomized complete block design with four replications during 2017 and 2018 cropping seasons. The finding showed that accessions 25, 19, and 28 are pollen sources for leaf length, accessions 31, 22, and 23 for leaves/plant, accessions 4, 18, and 27 performed best for seeds/pod and accessions 8, 11, and 7 for seed mass. The seed mass had a positive association with leaf length, leaf width, and plant height at maturity, seeds/capsule, seeds/loculi and 100 seed mass. The number of leaves/plant was influenced by leaf length, leaf width, and branch length. The path analysis for seed mass showed that branches/plant, seed mass/capsule, seeds/loculi, capsule mass marked a large contribution to seed yield. The indirect contribution of traits to leaves/plant was low in magnitude compared to the direct effect. The leaf length had the largest direct effect on the number of leaves/plant with its largest indirect effect through the reduction in seed mass. The direct contribution of leaf length to leaves/plant was masked by phenotypic expression of petal width. The number of branches/plant is a reliable index for improvement in seed yield. Hybridization among best-performing accessions for leaf number and seed yield will evolve new varieties through selection.